Serological surveillance of Trypanosoma evansi in Kazakhstani camels by complement fixation and formalin gel tests - Abay, Zhandos; Kudaibergenova, Zhadra; Bizhanov, Alim; Serikov, Maksat; Berdiakhmetkyzy, Salika; Arysbekova, Altynai; Aitlessova, Roza; Smadil, Temir; Kadyrov, Serikbay; Lessov, Berik; Sattarova, Rano; Kanatbayev, Serik; et al. (Frontiers in Veterinary Science, 2025)
IntroductionSurra, caused by Trypanosoma evansi (T. evansi), is a significant vector-borne disease of camels that leads to substantial economic losses in affected regions. This study was conducted to determine the seroprevalence of surra among dromedary (Camelus dromedarius) and Bactrian (Camelus bactrianus) camels in Kazakhstan.MethodsA cross-sectional survey was carried out between January and May 2024 in the Mangystau, Kyzylorda, and Turkestan regions. A total of 2,773 camel serum samples (1,045 males and 1,728 females) were collected and tested using the complement fixation test (CFT) and the formol gel test (FGT). Chi-square tests were applied to assess differences across age groups, sexes, and regions.ResultsAntibodies against T. evansi were detected in 113 camels (4.07%; 95% CI: 3.36–4.86) by CFT and in 276 camels (9.95%; 95% CI: 8.88–11.13) by FGT. Seroprevalence increased with age, with the highest rates observed in camels older than 12 years (5.93% by CFT and 26.27% by FGT). Females had significantly higher prevalence than males (CFT: 4.69% vs. 3.06%; FGT: 10.47% vs. 9.09%, p = 0.046). Regional variation was also noted, with the highest prevalence detected in Mangystau by FGT (65.0%).DiscussionThese findings confirm that camel surra is endemic in the surveyed regions of Kazakhstan. Both serological tests proved useful for large-scale screening of T. evansi, and the FGT, due to its higher sensitivity, is recommended as the preferred tool for field surveillance.